INTRADIALLYTIC EXERCISE-RANGE OF MOTION (IDE-ROM) AND CINNAMON AROMATHERAPY ON ANXIETY, FATIGUE AND SLEEP QUALITY IN HEMODIALYSIS PATIENTS: EXPERIMENT STUDY - Sri Sulistiyawati; Nur Hidaayah; Dyah Ika Krisnawati; Nursalam; Yanis Kartini; Chilyatiz Zahroh (Nursing Sciences Journal, 2026)
Routine hemodialysis patients frequently experience anxiety, chronic fatigue, and sleep disturbances, necessitating a holistic non-pharmacological approach. This study aims to analyze the effect of combined Intradialytic Exercise–Range of Motion (IDE-ROM) and cinnamon aromatherapy on anxiety, fatigue, and sleep quality among patient at RSUD Syarifah Ambami Rato Ebu Bangkalan. This quantitative research employed a quasi-experimental design with a pretest-posttest control group approach. Seventy respondents were selected through purposive sampling and divided into a control group (n=35) and an intervention group (n=35). The intervention group received a combination of IDE-ROM and cinnamon aromatherapy inhalation across six sessions over one month. Data were collected using the Zung Self-Rating Anxiety Scale (SAS), the Functional Assessment of Chronic Illness Therapy (FACIT) fatigue scale, and the Pittsburgh Sleep Quality Index (PSQI). Data analysis was performed using Paired t-tests and MANOVA. The intervention significantly affected all three variables (p < 0.05). MANOVA results indicated the strongest effect on sleep quality (p < 0.001), while the variables of anxiety (p = 0.348) and fatigue (p = 0.121) showed lower significance levels compared to sleep quality. The combination of IDE-ROM and cinnamon aromatherapy is effective in improving the physical and psychological conditions of patients. This intervention provides the most dominant influence on enhancing the sleep quality of the respondents.